2020
DOI: 10.21273/hortsci14584-19
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Propagation and NaCl Tolerance of the Multipurpose Medicinal Halophyte Limoniastrum monopetalum

Abstract: Limoniastrum monopetalum is an evergreen perennial shrub native to Mediterranean coastal sands and salt marshes. It has adapted to a variety of environmental stresses and is used in traditional medicine and as an ornamental plant. In the present study, an efficient micropropagation protocol for this species was developed to facilitate the production of selected genotypes and promote its wider use. Research has focused on the effects of various cytokinin types [benzyladenine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Addition of IBA to the medium did not affect rooting percentage, but it increased root number and reduced root length proportional to the increase of its concentration, while it promoted lateral shoot sprouting (Table 6, Figure 1K). Such negative relation between root number and root length has been shown also in micropropagation of carnation and the Mediterranean species Teucrium capitatum and Limoniastrum monopetalum (Papafotiou and Martini, 2016;Salehi, 2006;Martini and Papafotiou, 2020). Shoot clusters rooted at 97% on half-strength Hf MS and produced 8.7 roots of 1.1 cm length at average (n=46, Figure 1L).…”
Section: In Vitro Rooting and Ex Vitro Acclimatizationsupporting
confidence: 54%
“…Addition of IBA to the medium did not affect rooting percentage, but it increased root number and reduced root length proportional to the increase of its concentration, while it promoted lateral shoot sprouting (Table 6, Figure 1K). Such negative relation between root number and root length has been shown also in micropropagation of carnation and the Mediterranean species Teucrium capitatum and Limoniastrum monopetalum (Papafotiou and Martini, 2016;Salehi, 2006;Martini and Papafotiou, 2020). Shoot clusters rooted at 97% on half-strength Hf MS and produced 8.7 roots of 1.1 cm length at average (n=46, Figure 1L).…”
Section: In Vitro Rooting and Ex Vitro Acclimatizationsupporting
confidence: 54%
“…The results of our study showed that roots were unable to root on MS/2 nutrient medium free of auxins. For in vitro rooting, half-strength MS medium supplemented with 1.0 mg/l of IBA was most effective, which was consistent with the in vitro rooting studies of other woody plants [2,8].…”
Section: Resultssupporting
confidence: 85%
“…Axillary shoot culture was used to study antioxidative defense and osmotic adjustment of Sesuvium portulacastrum during high salinity [ 25 ]. Shoot cultures of Salicornia europaea [ 26 ], Salicornia brachiata [ 27 ] and Limoniastrum monopetalum [ 28 ] were used to reveal essentiality of NaCl for efficient in vitro propagation of these halophyte species. However, NaCl gradually reduced shoot proliferation in explants of Crithmum maritimum [ 29 ].…”
Section: Introductionmentioning
confidence: 99%